2014
DOI: 10.1155/2014/868753
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Attenuated Cardiac Hypertrophy Induced by Isoproterenol and Maintained Energy Homeostasis via Inhibiting NF-κB Activation

Abstract: Rapamycin, also known as sirolimus, is an immunosuppressant drug used to prevent rejection organ (especially kidney) transplantation. However, little is known about the role of Rapa in cardiac hypertrophy induced by isoproterenol and its underlying mechanism. In this study, Rapa was administrated intraperitoneally for one week after the rat model of cardiac hypertrophy induced by isoproterenol established. Rapa was demonstrated to attenuate isoproterenol-induced cardiac hypertrophy, maintain the structure inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…As previously reported (27)(28)(29), ISO treatment resulted in increased activity of mTOR, as evidenced by the increase in phospho-mTOR to total mTOR ratio in ISOtreated Mlip ϩ/ϩ when compared with saline-treated Mlip ϩ/ϩ hearts (Fig. 6F).…”
Section: Mlip Is Genetically Associated With and Required For Precocisupporting
confidence: 86%
“…As previously reported (27)(28)(29), ISO treatment resulted in increased activity of mTOR, as evidenced by the increase in phospho-mTOR to total mTOR ratio in ISOtreated Mlip ϩ/ϩ when compared with saline-treated Mlip ϩ/ϩ hearts (Fig. 6F).…”
Section: Mlip Is Genetically Associated With and Required For Precocisupporting
confidence: 86%
“…As an activator of autophagy, rapamycin has been shown to be able to prevent cardiac hypertrophy in animals subjected to thyroid hormone or isoprenaline treatment, and even to reverse stressinduced cardiac hypertrophy, leading to improved cardiac function [16,17]. Similar to previous data, the results of the present study using rapamycin treatment as a positive control in AB rats showed reproducible protective effects, including prevention of cardiac hypertrophy progression, retardation of remodeling, and inhibition of cardiomyocyte apoptosis, accompanied by activation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the hearts were rapidly excised, washed with ice-cold phosphate-buffered saline, dried and weighed to calculate heart-to-body weight (HW/BW) ratio. [19,22] The hearts were homogenized in phosphate-buffered saline, and supernatants were stored at À80°C for biochemical assays. Three hearts from each group were fixed in 10% neutral-buffered formal saline for histopathological study.…”
Section: Hemodynamic Measurements and Heart-to-body Weight Ratiomentioning
confidence: 99%